Community memories : a glimpse of African American life in Frankfort, Kentucky - Fletcher, Winona L.; Burton, Sheila Mason, 1948-; Wallace, James E., 1957-; Winter, Mary E., 1953-; Boyd, Douglas A., 1970-; Hardin, John (Kentucky Historical Society, 2003)
"To be sure, these photos and oral history excerpts offer only a brief glimpse into the everyday life of the African American community. There are undoubtedly aspects of that community that are not included at all; however, five main themes emerged in both the interviews and the images and became the subjects of distinct chapters within the book - the elusive concept of community is the overarching theme; the importance of family, and the significance of employment, religion, and education are the threads that combine to form the sense of community, togetherness, and belonging. Within these often-intertwined webs of social interaction, reside the stories, celebrations, songs, meeting places, and lore of Black residents in the Frankfort area."